Regionalisasi Wilayah Kabupaten Bantul (Suatu Kajian Untuk Kepentingan Perencanaan Pengembangan Wilayah) - Giyarsih, Sri Rum (Center for Research and Community Services ITB, 2001)
Regionalization is a method to understand a region based on the characteristic according to its potency and problems. Regionalization in relation with development is a regional grouping based on the possibì1iy of its development As a consequance regionalization assessment has become an important necessity for regional development planning. Based on the reasons mentioned above, this research is intended to: (1) arrange regions based on the potency of various development sectors, (2) identity leading sectors at each kecamatan, (3) utilize regionalization to determine regional priority and development policy.